2016
DOI: 10.1098/rstb.2015.0353
|View full text |Cite
|
Sign up to set email alerts
|

Functional magnetic resonance imaging in chronic ischaemic stroke

Abstract: Ischaemic stroke is the leading cause of adult disability worldwide. Effective rehabilitation is hindered by uncertainty surrounding the underlying mechanisms that govern long-term ischaemic injury progression. Despite its potential as a sensitive non-invasive in vivo marker of brain function that may aid in the development of new treatments, blood oxygenation level-dependent (BOLD) functional magnetic resonance imaging (fMRI) has found limited application in the clinical research on ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 78 publications
1
24
0
1
Order By: Relevance
“…Changes in amplitude and latency have even been demonstrated in both affected and unaffected hemispheres and are most prominent in, though not limited to, the first 3 weeks after stroke. 35,37 For a more extensive review of fMRI studies in stroke, see Lake et al 43 Importantly, changes in amplitude and latency often seem to co-occur, i.e. hemodynamically compromised vasculature shows a BOLD hemodynamic response function that is both reduced in amplitude and increased in latency.…”
Section: Blood Flow and Hemodynamicsmentioning
confidence: 99%
“…Changes in amplitude and latency have even been demonstrated in both affected and unaffected hemispheres and are most prominent in, though not limited to, the first 3 weeks after stroke. 35,37 For a more extensive review of fMRI studies in stroke, see Lake et al 43 Importantly, changes in amplitude and latency often seem to co-occur, i.e. hemodynamically compromised vasculature shows a BOLD hemodynamic response function that is both reduced in amplitude and increased in latency.…”
Section: Blood Flow and Hemodynamicsmentioning
confidence: 99%
“…Testing of this hypothesis and the design of novel therapeutic approaches based on hormonal (estrogen alone or in combination with progesterone or allopregnanolone) supplementation requires models that recapitulate the salient phases of focal cerebrovascular occlusion-reperfusion and the drop in ovarian hormones observed in the patient population following bilateral oophorectomy. The present study is the first to link in vivo neurovascular function, which has been demonstrated a sensitive assay of brain recovery [for review ( Lake et al, 2016 )], with circulating estrogen levels at the time of ischemia, providing initial evidence that the evolution of ischemic damage and recovery is affected by estrogen levels in a model of oophorectomy in mature females. Our model of oophorectomy reproduces the faster decrease in estrogen concentration observed in surgically induced menopause [vs. that of natural menopause in women ( Korse et al, 2009 )] and ET-1 model of focal cortical ischemia produces a precisely targeted necrotic core surrounded by a sizeable region of functionally-challenged peri-ischemic tissue ( Hossmann, 2008 , 2009 ).…”
Section: Discussionmentioning
confidence: 90%
“…Ovariectomy did not affect peri-lesional tissue volume, (Ovx: 1654.7 ± 504.6 mm 3 , n = 6 vs. Sham: 1513.1 ± 414.0 mm 3 , n = 6, p = 0.98, Student’s t -test, Figure 1Aiv ). Given the limited sensitivity of T 2 -weighted MRI in predicting vascular and functional recovery [( Girard et al, 2014 ) and for review ( Lake et al, 2016 )], CASL MRI data were collected and used to estimate resting brain perfusion and cerebrovascular reactivity to hypercapnia, a standard (pre)clinical test of brain vascular functioning. CASL maps overlaid on structural T 2 -weighted MR images from representative Sham and Ovx animals 3 weeks after surgery are shown in Figure 1 (resting perfusion in Figure 1B and cerebrovascular reactivity to hypercapnia in Figure 1C ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…За окремими прогнозними оцінками до 2050 року передбачається подвоєння кількості інсультів, особливо у пацієнтів старше 75 років [1,3]. Все частіше в фаховій літературі використовується термін «хронічний інсульт» під яким розуміють симптомокомплекс залишкового неврологічного дефіциту через 6 місяців або більше перенесеного інсульту [4,5]. Існують докази того, що рання активізація хворого є запорукою повноцінного функціонального відновлення, під яким розуміють досягнення оптимального фізичного стану, в тому числі функціональної, когнітивної, емоційної та соціальної активності [6,7].…”
Section: Yurivorokhta@gmailcomunclassified